2023
DOI: 10.1007/s10311-023-01581-7
|View full text |Cite
|
Sign up to set email alerts
|

Biofuel production, hydrogen production and water remediation by photocatalysis, biocatalysis and electrocatalysis

Abstract: The energy crisis and environmental pollution have recently fostered research on efficient methods such as environmental catalysis to produce biofuel and to clean water. Environmental catalysis refers to green catalysts used to breakdown pollutants or produce chemicals without generating undesirable by-products. For example, catalysts derived from waste or inexpensive materials are promising for the circular economy. Here we review environmental photocatalysis, biocatalysis, and electrocatalysis, with focus on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(34 citation statements)
references
References 617 publications
0
22
0
Order By: Relevance
“…To understand the sono-sorption behavior and the sonosorption capacity for Sr(II) and Ce(III) metal ions on the ST sorbent, the Langmuir (eqn (10) and ( 11)), 108 Freundlich (eqn ( 12)), 109 and Dubinin-Radushkevich (D-R) 110 isotherm models (eqn ( 13)-( 15)) were used to fit the experimental data. These models are expressed as follows: Langmuir:…”
Section: Sono-sorption Isotherm Studymentioning
confidence: 99%
See 2 more Smart Citations
“…To understand the sono-sorption behavior and the sonosorption capacity for Sr(II) and Ce(III) metal ions on the ST sorbent, the Langmuir (eqn (10) and ( 11)), 108 Freundlich (eqn ( 12)), 109 and Dubinin-Radushkevich (D-R) 110 isotherm models (eqn ( 13)-( 15)) were used to fit the experimental data. These models are expressed as follows: Langmuir:…”
Section: Sono-sorption Isotherm Studymentioning
confidence: 99%
“…They found that the best method is the adsorption process, which is due to its unique properties in terms of reducing time and obtaining a high removal rate of metal ions and radioactive isotopes using different adsorbents. [5][6][7][8][9][10] Lately, biomass materials like coconut shell activated carbon, 11,12 sawdust, [13][14][15] activated carbon, [16][17][18][19] natural materials, 20,21 activated carbon derived from pine sawdust, 22 magnetic plastic waste-biomass char composite (MPBC), 23 activated carbon and carbon nanotubes that synthesized from biomass, [24][25][26][27][28][29] .....etc., have been used as adsorbents to isolate heavy metal ions, organics, dyes and radioactive isotopes from contaminated water. Where, these biomass materials include numerous function groups as -COOH, -OH, and CO and these groups are associated with the element through ion-exchange, van der Waals interactions, complexation or co-precipitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process can be modulated through modification of their fundamental structure . However, their effectiveness as biocatalysts in the biomedical field remains uncertain since of their modest conductivity and larger band gap. , Enhancement of the electronic configuration and number of biologically active sites is an efficient approach for boosting their electrical conductivity as well as chemical–physical aspects enabling biocatalysis since these factors play a significant influence on catalytic performances. , Numerous techniques are aimed at improving a material’s catalytic effectiveness by offering a greater abundance of catalytic sites with an expanded surface area, such as the inclusion of additional substances or doping defect technology, the architecture of composite materials, and so on. , Among these, doping is a practical approach to augmenting the efficiency of biocatalytic processes through the incorporation of additional atoms within the mother metal oxide lattice structure. After successfully doping, the dopant can regulate the electronic configuration of the biocatalyst by boosting the electric charge carrier density and conductivity and further improving the active sites .…”
Section: Doped-iron Oxide Nanoparticles (Doped-ionps)mentioning
confidence: 99%
“…62,63 Enhancement of the electronic configuration and number of biologically active sites is an efficient approach for boosting their electrical conductivity as well as chemical− physical aspects enabling biocatalysis since these factors play a significant influence on catalytic performances. 64,65 Numerous techniques are aimed at improving a material's catalytic effectiveness by offering a greater abundance of catalytic sites with an expanded surface area, such as the inclusion of additional substances or doping defect technology, the architecture of composite materials, and so on. 66,67 Among these, doping is a practical approach to augmenting the efficiency of biocatalytic processes through the incorporation of additional atoms within the mother metal oxide lattice structure.…”
Section: Doped-iron Oxide Nanoparticles (Doped-ionps)mentioning
confidence: 99%